Himalaya Hai To Hum Hain - Pathak, Shekhar (JOURNAL OF INDIAN EDUCATION, 2013)
Himalaya, the ‘abode of snow’, is home not only to an imposing geological, geographical and biological diversity but also to a multitude of flourishing human concerns and constructs, from hunting-gathering communities to agrarian societies and their settled cultures and also to the economies of modern trade and industry. This mountain system has created and fostered a distinctive ecology that has become the basis for the existence of the natural as well as cultural systems of South Asia. From the east to the west, Himalaya stands like a sub-continental arc. In so many ways, it is dynamic and active. Its rich soil and water, in spreading abundant fertility and life in the plains below, transform the landscape extraordinarily; its communities and their cultures, which arrived and settled over millennia, have in turn spread out in many directions.